Analysis of the Effect of Labor Quantity on the Output Value of Micro-Industries in Indonesia Using Simple Linear Regression Method - Nugraha, Isna; An Khofiyah, Nida; Ramadhan, Gilang; Aryanti, Friska (UPN Veteran Jatim, 2025)
In the current era of globalization, rapid advancements are driving nations to compete in strengthening their economies. Companies and industrial enterprises play a vital role as economic units actively contributing to national economic activities. Economic growth is closely associated with the output value of industries, which is significantly influenced by the number of workers. This study aims to examine the effect of the number of workers in micro-industries on the output value of micro-industries in Indonesia. The research employs two variables: the independent variable (X), representing the number of micro-industry workers, and the dependent variable (Y), representing the output value of micro-industries. A simple linear regression analysis was applied to measure the extent of the relationship between these variables. The results show a regression equation of Y = 217.512,365 + 46,669X with a coefficient of determination (R²) of 0,896, indicating that 89,6% of the variation in output value can be explained by the number of micro-industry workers. This suggests a strong influence of labor quantity on micro-industry output in Indonesia.